Comparison between negative pressure and conventional wound dressing for diabetic foot ulcer: A systematic review - I Gusti Ayu Agung Bella Jayaningrum; Anak Agung Istri Ayu Detritha Sarasmartha Putri; Pretty Clarresa (DiscoverSys Inc., 2020)
Background: Diabetic foot ulcer (DFU) is a common complication of diabetes mellitus (DM), resulting in loss of limb or life. Negative pressure wound therapy (NPWT) is an emerging therapeutic option in the management of DFU. This study aims to compare the efficacy of NPWT to conventional moist wound dressing in the management of DFU.Methods: Literature was searched from online public scientific databases, including PubMed, Google Scholar, ScienceDirect, and Portal Garuda. Our review included clinical trials and analytic studies comparing NPWT and conventional moist dressing to treat DFU published in 2017 or later. Outcome measures include the proportion of wound healing, healing time, ulcer size reduction, granulation time, amputation, infection, and bleeding.Results: We include 11 articles, including eight randomized clinical trials (RCTs), two retrospective analytic studies, and one non-random clinical trial. There was methodological variation between studies on the application of NPWT, outcome measures reported, and length of follow up. Results mostly showed NPWT yielded a higher proportion of complete wound healing, shorter healing time, granulation time, and faster ulcer size reduction rate. However, NPWT was not associated with a reduction of amputation risks.Conclusions: Our review found NPWT was superior in short-term treatment outcomes such as granulation time and wound closure; however, there was no difference in reducing amputation risk between NPWT and conventional moist dressing. Results are inconclusive due to variation in methodologies of included articles.